'It's risky to walk in the city with syringes': understanding access to HIV/AIDS services for injecting drug users in the former Soviet Union countries of Ukraine and Kyrgyzstan - Harmer Andrew; Brugha Ruairi; Bogdan Daryna; Spicer Neil; Murzalieva Gulgun; Semigina Tetiana (BMC, 2011)
Abstract Background Despite massive scale up of funds from global health initiatives including the Global Fund to Fight AIDS, Tuberculosis and Malaria (Global Fund) and other donors, the ambitious target agreed by G8 leaders in 2005 in Gleneagles to achieve universal access to HIV/AIDS treatment by 2010 has not been reached. Significant barriers to access remain in former Soviet Union (FSU) countries, a region now recognised as a priority area by policymakers. There have been few empirical studies of access to HIV/AIDS services in FSU countries, resulting in limited understanding and implementation of accessible HIV/AIDS interventions. This paper explores the multiple access barriers to HIV/AIDS services experienced by a key risk group-injecting drug users (IDUs). Methods Semi-structured interviews were conducted in two FSU countries-Ukraine and Kyrgyzstan-with clients receiving Global Fund-supported services (Ukraine n = 118, Kyrgyzstan n = 84), service providers (Ukraine n = 138, Kyrgyzstan n = 58) and a purposive sample of national and subnational stakeholders (Ukraine n = 135, Kyrgyzstan n = 86). Systematic thematic analysis of these qualitative data was conducted by country teams, and a comparative synthesis of findings undertaken by the authors. Results Stigmatisation of HIV/AIDS and drug use was an important barrier to IDUs accessing HIV/AIDS services in both countries. Other connected barriers included: criminalisation of drug use; discriminatory practices among government service providers; limited knowledge of HIV/AIDS, services and entitlements; shortages of commodities and human resources; and organisational, economic and geographical barriers. Conclusions Approaches to thinking about universal access frequently assume increased availability of services means increased accessibility of services. Our study demonstrates that while there is greater availability of HIV/AIDS services in Ukraine and Kyrgyzstan, this does not equate with greater accessibility because of multiple, complex, and interrelated barriers to HIV/AIDS service utilisation at the service delivery level. Factors external to, as well as within, the health sector are key to understanding the access deficit in the FSU where low or concentrated HIV/AIDS epidemics are prevalent. Funders of HIV/AIDS programmes need to consider how best to tackle key structural and systemic drivers of access including prohibitionist legislation on drugs use, limited transparency and low staff salaries within the health sector.